Development of Two Phase H-bridge Converter for 250W Switched Reluctance Machine - Ahammed, Shaik A.; Seshadri, Arjun; Chokkalingam, Lenin N. (Recent Advances in Electrical & Electronic Engineering, 2020)
Background: Advancements in Power Electronics made a huge breakthrough in the industrial sector majorly in the development of Switched Reluctance Machines (SRM). The main objective of this paper is to develop a two Phase H-bridge converter for 250W SRM and compare its advantages and disadvantages over the other converters. Methods: A time based simulation has been carried out to evaluate the performance of the converter at various loads. Different parameters of the machine and converter are studied and the results are verified experimentally. Results: The obtained test results of the converter performance are found to be in good agreement with the simulation and the efficiency of the converter is compared with the existing R-Dump topology. Conclusion: It is concluded that the proposed H-Bridge converter for a two phase SRM is better than the R-Dump converter in terms of efficiency and reduced size.
Keywords: power converters